2021
DOI: 10.4103/jfmpc.jfmpc_1505_20
|View full text |Cite
|
Sign up to set email alerts
|

Family physicians/GP and Internist opinions, familiarity and practice behaviour regarding clinical practice guidelines (CPGs) of common medical conditions in Nigeria

Abstract: Background: Few studies exist on physicians' opinions, attitudes, familiarity and practice behaviour regarding clinical practice guidelines in sub-Saharan Africa. Objectives: To determine the opinions, familiarity, and practice behaviour regarding clinical practice guidelines (CPGs) and factors associated with their use among internists and family physicians/GP in Nigeria. Methods: A semi-structured questionnaire regarding guidelines of five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Nonetheless, guideline familiarity was significantly associated with all practice behaviors (assess, advise, refer, share/coordinate) among both provider types, demonstrating the importance of guideline familiarity in influencing clinical practice behaviors. Low familiarity with guidelines has been found in studies across a range of health care providers, in addition to low familiarity specific to the prenatal oral health guidelines among prenatal and oral health providers [ 18 , 25 27 ]. For example, in one study, lack of guideline familiarity was a primary barrier to physician adherence [ 25 ], while in another study, physician familiarity with five common clinical guidelines was significantly associated with practice behavior change relating to two of the guidelines [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, guideline familiarity was significantly associated with all practice behaviors (assess, advise, refer, share/coordinate) among both provider types, demonstrating the importance of guideline familiarity in influencing clinical practice behaviors. Low familiarity with guidelines has been found in studies across a range of health care providers, in addition to low familiarity specific to the prenatal oral health guidelines among prenatal and oral health providers [ 18 , 25 27 ]. For example, in one study, lack of guideline familiarity was a primary barrier to physician adherence [ 25 ], while in another study, physician familiarity with five common clinical guidelines was significantly associated with practice behavior change relating to two of the guidelines [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Low familiarity with guidelines has been found in studies across a range of health care providers, in addition to low familiarity specific to the prenatal oral health guidelines among prenatal and oral health providers [ 18 , 25 27 ]. For example, in one study, lack of guideline familiarity was a primary barrier to physician adherence [ 25 ], while in another study, physician familiarity with five common clinical guidelines was significantly associated with practice behavior change relating to two of the guidelines [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the prevalence of regular exercise among patients with HTN 11–13 ; however, these studies had small sample sizes and were limited to patients in low‐ and middle‐income countries, including Ethiopia, Iran, and China 11–13 . Moreover, medical resources, healthcare systems, and treatment strategies available in low‐ and middle‐income countries differ from those in high‐income countries 5,9,14–16 . Therefore, exercise habits in patients with HTN may differ among low‐, middle‐, and high‐income countries.…”
Section: Introductionmentioning
confidence: 99%
“… 11 , 12 , 13 Moreover, medical resources, healthcare systems, and treatment strategies available in low‐ and middle‐income countries differ from those in high‐income countries. 5 , 9 , 14 , 15 , 16 Therefore, exercise habits in patients with HTN may differ among low‐, middle‐, and high‐income countries. Hence, it is crucial to assess the proportion of patients engaging in exercise in each country in order to enhance the approach to exercise therapy in the healthcare system.…”
Section: Introductionmentioning
confidence: 99%